Strategic Business Process Analysis: A Procedure Model to Align Business Strategy with Business Process Analysis Methods - Lederer, Matthias; Schott, Peter; Huber, Sebastian; Kurz, Matthias (S-BPM ONE Running Solutions: 5th International Conference S-BPM ONE 2013 Proceedings, 2013)
In literature and business practice, implementing the business strategy and analyzing business processes is often addressed separately although business processes are regarded as a competitive key resource. In many businesses, it is unclear which systematic approach is most appropriate to identify process analysis methods which support the achievement of strategic objectives best. This contribution proposes an association model for the systematic combination of corporate strategy and business process analysis methods: First, it describes how a corporate strategy can be formalized. Then, a system is designed that rates known process analysis methods according to their support of the process strategy. Users of the model only have to rate the importance of strategy classes on a numerical scale. In order to validate the model, it has been tested during expert interviews and by applying it for real processes from different companies. © 2013 Springer-Verlag.
WiSo2-Import:2015-10-05:581
Keywords: Business Process Strategy; Process Analysis Methods; Strategy Analysis